Quantum Learning Membangun Pendidikan Karakter Kejujuran Siswa - Sulistia Ningsih; Ika Rahmawati (Proceedings of The ICECRS, 2019)
Attending education for developing the potential of domain students, affective and psychomotor. One of domains in achieving elementary school education is fundamental education to build the character of children while sitting in school. One of the values of character education is honest behavior. Honesty is a behavior that is shown to be in accordance with the real conditions without manipulating by lying. Methods of research using quantum learning methods, followed by quantitative methods with data collection techniques using open poll and supporting tools during the research voucher honesty. The study subject of elementary school students of Muhammadiyah 2 Kauman Surakarta class 4A with 30 students. The results of the study that there are positive behaviors from students in acting honestly without teacher observation in class. This is evidenced from the sale of vouchers, where the number of vouchers purchased and the amount of money received are appropriate.